Determination of filler content for natural filler polymer composite by thermogravimetric analysis - Nabinejad, O.; Sujan, D.; Rahman, Muhammad; Davies, Ian (Kluwer Academic Publishers, 2015)
© 2015 Akadémiai Kiadó, Budapest, Hungary. Determination of filler content by thermogravimetric (TG) analysis is commonly utilized to investigate the effectiveness of processing methods for composite materials and to quantify the dispersion of filler within the matrix. However, the existing analysis method is not capable of accurately predicting the filler content for natural fiber composites for the case where thermal degradation of the filler and matrix occurs within similar temperature ranges. In the present study, the authors have proposed a generic equation for the determination of filler content which can be utilized for any given range of thermal degradation temperatures in natural filler polymer composites. Oil palm shell unsaturated polyester composites were selected to verify the proposed equation using the TG test with the results indicating good agreement between the estimated and experimental filler contents with a maximum error on the order of 10 %. The suggested technique provides a simple, yet generic, approach to determining the filler content of green or lignocellulose-based polymer composites by TG analysis.